2018
DOI: 10.1097/md.0000000000010637
|View full text |Cite|
|
Sign up to set email alerts
|

Marital status and survival in patients with rectal cancer

Abstract: To examine the impact of marital status on overall survival (OS) and rectal cancer-specific survival (RCSS) for aged patients.We used the Surveillance, Epidemiology and End Results database to identify aged patients (>65 years) with early stage rectal cancer (RC) (T1-T4, N0, M0) in the United States from 2004 to 2010. Propensity score matching was conducted to avoid potential confounding factors with ratio at 1:1. We used Kaplan-Meier to compare OS and RCSS between the married patients and the unmarried, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…In this study,the routinely available characteristics of the patients were extracted from the database.Based on these,a nomogram was developed and validated.The model performance of the In agreement with other type of NSCLC,the age and sex were all important predictors for CSS of LCLC [13].Old age and male patients were associated with worse prognosis.In order to get better discrimination for the nomogram model,According to Harrell's guidelines,in this study,patients age were determined into two groups [14].Seventy-seven years old was the best cutoff point.At present,an consistent conclusion was not reached for the CSS disparities of patients with lung cancer for different race [15].In genaral,better CSS outcomes would be seen in race with higher health awareness,that the treatment in these races would be more active.In this study,as for LCLC,the significantly different influence of race for patient's CSS was seen both in univariable and multi-variable analysis.The CSS outcome for other race is better than the White race.Treatment activity might be a possible explanation for this phenomenon,another reason might be attributed to the sample of the SEER database,that small proportion of other race was collected in the database,which might affect the statistical results for this study.As a most common used tumor associated indices,the AJCC stage still contributed most for the established nomogram model,which is in line with other type of NSCLC [16].Tumour size is an important indicator for T stage,in this study,its was also found to be an independent risk factor for LCLC.It could be confirmed that patients with a tumour size >41mm show less CSS time than that <=41mm with the maximally selected rank statistics.Surgery is the domain treatment for many type of lung cancer.In this study,surgery was also found to be an important treatment for LCLC that patients with surgery had a greatly decrease in cancer-specific death.Marital status has been confirmed to be associated with the CSS in a series of cancer [17][18][19][20][21].This phenomenon, in our present study was consistent with the previous study that married LCLC patients represented for lower nomogram scores had CSS benefit compared with other types of marital status.…”
Section: Discussionsupporting
confidence: 93%
“…In this study,the routinely available characteristics of the patients were extracted from the database.Based on these,a nomogram was developed and validated.The model performance of the In agreement with other type of NSCLC,the age and sex were all important predictors for CSS of LCLC [13].Old age and male patients were associated with worse prognosis.In order to get better discrimination for the nomogram model,According to Harrell's guidelines,in this study,patients age were determined into two groups [14].Seventy-seven years old was the best cutoff point.At present,an consistent conclusion was not reached for the CSS disparities of patients with lung cancer for different race [15].In genaral,better CSS outcomes would be seen in race with higher health awareness,that the treatment in these races would be more active.In this study,as for LCLC,the significantly different influence of race for patient's CSS was seen both in univariable and multi-variable analysis.The CSS outcome for other race is better than the White race.Treatment activity might be a possible explanation for this phenomenon,another reason might be attributed to the sample of the SEER database,that small proportion of other race was collected in the database,which might affect the statistical results for this study.As a most common used tumor associated indices,the AJCC stage still contributed most for the established nomogram model,which is in line with other type of NSCLC [16].Tumour size is an important indicator for T stage,in this study,its was also found to be an independent risk factor for LCLC.It could be confirmed that patients with a tumour size >41mm show less CSS time than that <=41mm with the maximally selected rank statistics.Surgery is the domain treatment for many type of lung cancer.In this study,surgery was also found to be an important treatment for LCLC that patients with surgery had a greatly decrease in cancer-specific death.Marital status has been confirmed to be associated with the CSS in a series of cancer [17][18][19][20][21].This phenomenon, in our present study was consistent with the previous study that married LCLC patients represented for lower nomogram scores had CSS benefit compared with other types of marital status.…”
Section: Discussionsupporting
confidence: 93%
“…The assumption of proportional hazards was evaluated by examining the scaled Schoenfeld residuals. Based on previous studies, we adjusted for the demographic variables, biological factors, and treatment (gender, age at diagnosis, stage, grade, site, morphology, chemotherapy status, surgery, and radiotherapy status) 15 , 18 , 31 . The stepwise selection method with P < 0.15 as the criterion for entry and P > 0.05 as the criterion for removal was used to select covariates for the final multivariate models.…”
Section: Methodsmentioning
confidence: 99%
“…The survival advantage of married patients is proportionally associated with the stage at diagnosis, with the highest survival advantage in stage III CRC 16 . Nonetheless, in multivariate analyses, adjusted for age at diagnosis, the survival advantage tends to reduce 13 or dissipate in rectal cancer patients with multivariate adjustment for demographic variables, stage, and treatment 18 . A Chinese study assessing CRC survival in surgically treated colon cancer patients reported that married patients had higher survival than unmarried patients, despite a similar stage of cancer and adjuvant therapy use 15 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the article, “Marital status and survival in patients with rectal cancer: A population-based STROBE cohort study”, [ 1 ] which appeared in Volume 97, Issue 18 of Medicine , Zhuyue Li and Kang Wang are co-first authors.…”
mentioning
confidence: 99%